Analisis Mutu Pelayanan Kesehatan Ibu dan Bayi oleh Tenaga Kesehatan dan Kader Posyandu di Wilayah Kerja Puskesmas Niki-Niki - Laura Patrisia Betty; Yoseph Kenjam; Indriati A. Tedju Hinga (Lontar : Journal of Community Health, 2019)
Integrated Healthcare Center (Posyandu) is one of the societies based on health service: is held from, by and for the society aimed to decrease the mortality of children and mothers. So, it needs the maximal and the quality service by the health workers and Posyandu cadres. This study aimed to analyze the quality of maternal and child healthcare by health workers and Posyandu cadres in the work area of Niki-Niki Public Health Center in 2019. The population of this study is all mothers who used the Posyandu service and the sample is 90 mothers. This is a quantitative study with cross-sectional study design. Results showed the quality of maternal and child healthcare is reviewed by five dimensions of the health quality service; the range of health workers' performance about 3,70 (very satisfying), the range of the interests is about 3,97 (very interesting), and the suitability between the performance and interests is about 93,32 percent (not qualified). And, the range of Posyandu cadres' performance is about 3,44 (very satisfying), the range of the interests is about 3,96 (very interesting), so the suitability of performance and interests is about 86,80 percent (not qualified). It needs to improve the quality of maternal and child healthcare by health workers and Posyandu cadres.